Arsenic Trioxide and Artemisinin Act Synergistically to Kill Tumor Cells In Vitro - Zhao, Xiaoyan; Yang, Sen; Zhang, Duoduo; Li, Zhubo; Huang, Chengzhi (Anti-Cancer Agents in Medicinal Chemistry, 2018)
Background: Arsenic trioxide (As2O3), which has been shown to be effective in treating leukemia and other solid tumors, was strictly restricted in clinical application due to its severe toxicity. The present study was performed to explore whether the combination of As2O3 and artemisinin could produce a more powerful anticancer effect and reduce the toxicity of As2O3. Method: MTT assay was performed to detect the cell viability of A549, Hela and HepG2 cells treated with As2O3 and artemisinin. Combination Index (CI) analysis was carried out to evaluate the synergistic effect of As2O3 and artemisinin. Wound healing assay was performed to evaluate the migration rate. Fluorescent microscopy measurements and flow cytometry were used to evaluate the apoptosis. Result: Reactive Oxygen Species (ROS) was detected with DCFH-DA. The cell proliferation assay indicated that artemisinin significantly enhanced the inhibitory effect of As2O3 in a dose and time-dependent manner (P<0.01). Combination Index (CI) analysis further demonstrated that combining artemisinin with As2O3 generated synergistic effects in A549 (CI=0.65±0.05), Hela (CI=0.68±0.07) and HepG2 (CI=0.47±0.01) cells. The combination of these two drugs also evidently reduced the cell migration rate. Artemisinin also enhanced the apoptosis, necrosis in As2O3- treated A549 and Hela cells. Combination of As2O3 and artemisinin significantly induced more apoptosis (22.1%) than As2O3 (5.68%) or ART (5.93%) alone in Hela cells. In addition, ROS levels were increased obviously by combining artemisinin with As2O3. Conclusion: The present study indicated that combining artemisinin with As2O3 would be a novel therapeutic strategy for cancer therapy.
Keywords: synergistic effect